2004
DOI: 10.1242/jeb.01074
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments of gastric pH, motility and temperature during long-term preservation of stomach contents in free-ranging incubating king penguins

Abstract: Male king penguins are able to store undigested food in their stomach for up to 3 weeks during their incubation fast, which evidently implies some modification of their digestive process. Using small electronic recorders, we studied the change in gastric pH, motility and temperature during the first week of food storage. The pH could be maintained at values as high as 6 throughout the incubation fast, a pH that is unfavourable for avian gastric proteinase activity. Gastric motility was never completely inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…These devices record temperature during passage through the gastrointestinal tract and have been used widely on relatively large species and in humans [10,63,64]. Recording duration is determined by gut passage rate, which may vary from hours to weeks but in large ruminants devices have been retained for up to 4 years (retention time was actually improved by increasing the size of the device) [56].…”
Section: Gastrointestinal Devicesmentioning
confidence: 99%
“…These devices record temperature during passage through the gastrointestinal tract and have been used widely on relatively large species and in humans [10,63,64]. Recording duration is determined by gut passage rate, which may vary from hours to weeks but in large ruminants devices have been retained for up to 4 years (retention time was actually improved by increasing the size of the device) [56].…”
Section: Gastrointestinal Devicesmentioning
confidence: 99%
“…It is known that the gastric pH in the penguin is variable. It was reported that the stomach pH of the king penguin was close to 4 at the beginning of the incubation fast, gradually increased in a few days, and could be maintained at values as high as 6 during the incubating fast (Gauthier-Clerc et al 2002;Thouzeau et al 2004). They argued that high pH might contribute to preservation of stomach contents during a long-term fast.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of penguins, captured food is stored in the stomach (Croxall 1987). The gastric pH of king penguins ranges from 2 to 4 in nonfasting periods (Gauthier-Clerc et al 2002;Thouzeau et al 2003Thouzeau et al , 2004, indicating secretion of gastric acid in the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…26,28 Many reports have suggested that the gastric pH varies from 2.5 to 3.7 in the fasting state due to declined secretion of hydrochloric acid by parietal cells. 26,28,29 Since the formulations of this study would be administrated under the fasting state during in vivo studies, the pH 2.5 simulated gastric juice was selected as the release media to illustrate the releases of the coated nanoemulsion, uncoated nanoemulsion, and multiple emulsion. The crosslinking complex prevented the emulsion inversion and then avoided insulin release from the inner phase in simulated gastric environment because of the tight Alg pre-gel network at low pH.…”
Section: Insulin Leakage From Coated Nanoemulsion In Simulated Gastrimentioning
confidence: 99%